Response of Factor VIII and IX-Deficient Blood to Wild Type and High Membrane Affinity Mutant Factor VIIa in an In Vitro Whole Blood Clotting Assay: Possible Correlation to Clinical Outcome - Henderson, Nicole; Key, Nigel S.; Christie, Beverly; Kisiel, Walter; Foster, Donald; Nelsestuen, Gary L. (Thrombosis and Haemostasis, 2002)
A modified form of the activated whole blood clotting time was used to evaluate response of blood from hemophilia patients to factor VIIa. Repeated assays of individuals over a one-year period showed consistency for each individual and significant difference between individuals. Four hemophilia patients with inhibitors gave low response to factor VIIa in the assay and were characterized as low or moderate clinical responders to factor VIIa therapy. Another four patients with moderate to good clinical responsiveness to factor VIIa therapy showed a strong response to factor VIIa in the assay. A factor VIIa mutant with enhanced membrane affinity showed 10 to 13-fold higher activity than wild type factor VIIa. The results may justify larger studies to determine the utility of this assay for evaluation of patient responsiveness and to set factor VIIa therapy levels.
Keywords: Factor VIIa; hemophilia